Cultivating Online Fun Fatwa in Contemporary Indonesia: Millennial, Piety, and New Religious Authority - Fitriansyah, Nuzul (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2023)
The digital culture has made the internet a significant source of knowledge for millennials. The fast access to information has made them associated with instant culture and bandwagon effect: they behave and adapt to popular trends and demand instant pleasurable activities. In this case, the phenomenon influences how they seek religious advice (fatwa). Pleasure and piety become parts of millennials’ religiosity: they want to look pious yet casual and trendy. This article closely examines a millennial hadrami-descent preacher, Habib Ja‘far. It investigates how he builds his religious authority among millennials and the youth by cultivating his online and fun fatwas. Habib Ja‘far’s YouTube channel is the main data source in this case. Employing qualitative research with netnography method and Slama’s theory on “mediated intimacy”, This study found that a mufti (a man who gives religious advice) must adapt to the changes in how people seek religious advice (fatwa) to gain authority. The more skilled he is at adapting, the more authoritative he will be. In Habib Ja‘far case, his adaptability to youth culture and social media has made him a new religious authority. His da’wa model using social media by collaborating with various speakers from different perspectives can engage a wider audience and make da’wa more entertaining, accepted, and informative toward the fun and easy side of religion without hurting its sacredness.